Budget-impact analysis for pleuroscopy in the diagnosis of undifferentiated pleural effusion. Issue 3 (2nd July 2020) - Dhaliwal, Inderdeep; Gillett, Daniel; Train, Emma; Amjadi, Kayvan; Mitchell, Michael; Johnson, Ana
Abstract: Total Canadian health expenditure has been increasing over the past 40 years to a total of 248 billion dollars (2017 Canadian Dollars). In 2017, the Canadian Institute for Health Information forecasted that hospital spending would reach 28.3% of total health expenditure. Innovation to reduce costs while improving care is necessary to maintain a high quality, sustainable healthcare system. Patients with malignant pleural effusion (MPE) are suffering from advanced cancer; providers should support an increased focus on interventions that maximize patients' time in their home environment. Video-assisted Thoracoscopic Surgery Pleuroscopy (VATS-P) and Medical Pleuroscopy (MP) are two equivalent procedures in the diagnosis of MPE. The purpose of this study was to model the 5-year budget impact of adopting the MP procedure from the perspective of the hospital system. Pleuroscopy cost data were collected from 2 tertiary, academic hospitals in Ontario and from published literature. Resources including: hospitalization, RN staffing, laboratory/diagnostics and allied health were created using hospital administrative data through the Ontario Case-Costing Initiative (OCCI). The cost model was conducted using OCCI data and cost data from published literature, for the years 2018–2023. Base case analysis shows the mean per-procedure costs of MP was 6, 146.16 lower than VATS-P. Budget impact for a shift from VATS-P to MP showed potential savings of 10, 243, 088.74 (2023 Canadian dollars) (−41.6%) for pleuroscopy in Ontario over 5 years (n = 1, 616). In conclusion, this paper describes the significant cost savings for the hospital system from a shift to MP from VATS-P for the diagnosis of undifferentiated pleural effusion.